Making sense of global key account management (GAM): a case study from Japan. Issue 7 (5th October 2018) - Ellis, Nick; Iwasaki, Akihito
Abstract : Purpose: The purpose of this paper is to investigate the relevance to situated managerial practice of the implementation frameworks contained in the global (key) account management (GAM) literature and to explore what specific GAM-related issues may be faced by key account managers working for an MNC based in Japan. Design/methodology/approach: Following a critical literature review, including a discussion of sales management in Japan, an exploratory case study is conducted of a chemical supplier that claims to be making the transition toward GAM. Findings: The findings confirm that intra-organizational contextual and cultural factors appear to influence the adoption of GAM programs by the focal firm. This suggests there is not a "one size fits all" strategic pathway to implementing GAM, and that western theoretical perspectives on KAM/GAM do not appear to have permeated the sense-making of some Japanese managers. Research limitations/implications: While the study indicates that the US/European approach to KAM and GAM does not appear to fit well with the Japanese business culture, this conclusion must come with the caveat that this is not necessarily a generalizable case. Originality/value: Much of the prior B2B marketing literature on KAM and GAM has investigated only western firms. This is possibly the first empirical research on GAM in a Japanese company. The paper offers a number of implications for theory and ponders the wisdom of making recommendations from such a culture-bound study.